2011
DOI: 10.1182/blood-2010-05-282574
|View full text |Cite
|
Sign up to set email alerts
|

Sbds is required for Rac2-mediated monocyte migration and signaling downstream of RANK during osteoclastogenesis

Abstract: Shwachman-Diamond syndrome (SDS) results from mutations in the SBDS gene, characterized by exocrine pancreatic insufficiency and hematologic and skeletal abnormalities. Neutropenia and neutrophil dysfunction are hallmark features of SDS; however, causes for the bone defects are unknown. Dysfunction of boneresorbing osteoclasts, formed by the fusion of monocytic progenitors derived from the same granulocytic precursors as neutrophils, could be responsible. We report that Sbds is required for in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 53 publications
2
32
0
1
Order By: Relevance
“…Finally, proteins were concentrated in Pierce protein concentrators, and protein concentration and purity were assessed by SDS-PAGE followed by Coomassie staining. Control experiments and data from previous studies 20,21 have verified that addition of TAT-Rac-WT rescues ROS generation and chemotaxis in leukocytes (data not shown).…”
Section: Tat-protein Transductionmentioning
confidence: 99%
“…Finally, proteins were concentrated in Pierce protein concentrators, and protein concentration and purity were assessed by SDS-PAGE followed by Coomassie staining. Control experiments and data from previous studies 20,21 have verified that addition of TAT-Rac-WT rescues ROS generation and chemotaxis in leukocytes (data not shown).…”
Section: Tat-protein Transductionmentioning
confidence: 99%
“…Thus, the primary defect underlying SDS is distinct from the other ribosomopathies associated with hematological disease. We suggest that the diverse alternate functions proposed for SBDS in mammalian cells (Wessels et al 2006;Austin et al 2008;Rujkijyanont et al 2008;Ball et al 2009;Leung et al 2010) are downstream secondary consequences of the primary defect in 60S ribosomal subunit maturation. How do we explain the SDS phenotype?…”
Section: Sds As a Ribosomopathymentioning
confidence: 99%
“…Although cosedimentation of human SBDS with free cytoplasmic 60S ribosomal subunits in sucrose gradients (Ganapathi et al 2007) would be consistent with a conserved role for SBDS in 60S subunit maturation, the current model in mammalian cells posits that eIF6 removal is triggered following phosphorylation of Ser 235 by protein kinase C (PKC) and RACK1 (receptor for activated protein C) (Ceci et al 2003). Furthermore, diverse alternate functions for SBDS in mammalian cells have been suggested, including mitotic spindle stabilization (Austin et al 2008), chemotaxis (Wessels et al 2006), Fas ligand-induced apoptosis (Rujkijyanont et al 2008), cellular stress responses (Ball et al 2009), and Rac2-mediated monocyte migration (Leung et al 2010). Thus, despite the prior genetic studies in yeast, the mechanism of eIF6 release in mammalian cells is controversial, biochemical evidence supporting direct catalysis of eIF6 release by SBDS and EFL1 in eukaryotic cells is currently lacking, and the specific function of the SBDS protein, its mode of action, and the molecular mechanism of the cooperative interaction with EFL1 remain obscure.…”
mentioning
confidence: 99%
“…Indeed, Rac2 activation downstream the signaling pathway of Sbds, a poorly characterized ribosome-related protein, and Rac1 activation upon interaction of the cytoplasmic tail of matrix metalloprotease MT1-MMP with p130Cas, are required for precursors migration. 37,38 Similarly, filamin A regulates actin dynamics that control M-CSF-dependent precursors migration via Rac1 and Cdc42 combined activation. 39 Besides, we showed that the atypical Rho GTPase RhoU, which expression is strongly induced during early osteoclastogenesis, is involved in osteoclast precursors fusion.…”
Section: E28119-4mentioning
confidence: 99%